Metode Band-Limited Phase Only Correlation (BLPOC) untuk Identifikasi Plat Kendaraan - Fitri Arnia; Syahrul Wahyudi; Siti Aisyah (Jurnal Rekayasa Elektrika, 2012)
Digital image processing and computer vision technologies have developed so rapidly and have numerous applications. Automatic lisence plate recognition systems (ALPRS) based on those technologies are not exceptions. In general, the ALPRSs required several steps including image capturing, plate location searching, character segmentation and character recognition. Successful of the whole systems depended heavily on the used segmentation method. A common drawback of many segmentation techniques is that they are very sensitive to illumination variability. The paper proposed a method for license plate recognition based on correlation of phase componenet with limited bandwidth. The method is widely known as band-limited phase only correlation (BLPOC). The method compared input plate’s image with plate’s images in the database. Based on simulation, detection rate can achieve 90% if an appropriate threshold value was selected.